Supervised Obesity Reduction Trial for AF ablation patients: results from the SORT-AF trial. Issue 10 (22nd April 2021) - Gessler, Nele; Willems, Stephan; Steven, Daniel; Aberle, Jens; Akbulak, Ruken Oezge; Gosau, Nils; Hoffmann, Boris A; Meyer, Christian; Sultan, Arian; Tilz, Roland; Vogler, Julia; Wohlmuth, Peter; et al.
Abstract: Aims: Weight management seems to be beneficial for obese atrial fibrillation (AF) patients; however, randomized data are sparse. Thus, this study aimed to investigate the influence of weight reduction on AF ablation outcomes. Methods and results: SORT-AF is an investigator-sponsored, prospective, randomized, multicentre, and clinical trial. Patients with symptomatic AF (paroxysmal or persistent) and body mass index (BMI) 30–40 kg/m 2 underwent AF ablation and were randomized to either weight-reduction (group 1) or usual care (group 2), after sleep–apnoea–screening and loop recorder (ILR) implantation. The primary endpoint was defined as AF burden between 3 and 12 months after AF ablation. Overall, 133 patients (60 ± 10 years, 57% persistent AF) were randomized to group 1 ( n  = 67) and group 2 ( n  = 66), respectively. Complications after AF-ablation were rare (one stroke and no tamponade). The intervention led to a significant reduction of BMI (34.9 ± 2.6–33.4 ± 3.6) in group 1 compared to a stable BMI in group 2 ( P  < 0.001). Atrial fibrillation burden after ablation decreased significantly ( P  < 0.001), with no significant difference regarding the primary endpoint between the groups ( P  = 0.815, odds ratio: 1.143, confidence interval: 0.369–3.613). Further analyses showed a significant correlation between BMI and AF recurrence for patients with persistent AF compared with paroxysmal AF patients ( P  = 0.032). Conclusion: The SORT-AF study shows that AF ablation is safe and successful in obese patients using continuous monitoring via ILR. Although the primary endpoint of AF burden after ablation did not differ between the two groups, the effects of weight loss and improvement of exercise activity were beneficial for obese patients with persistent AF demonstrating the relevance of life-style management as an important adjunct to AF ablation in this setting. Trial registration number: NCT02064114.